2001
DOI: 10.1016/s0301-0511(01)00066-7
|View full text |Cite
|
Sign up to set email alerts
|

Vagal cardiac control throughout the day: the relative importance of effort–reward imbalance and within-day measurements of mood, demand and satisfaction

Abstract: The effects of variables derived from a work stress theory (the effort-reward imbalance theory) on the power in the high frequency (HF -HRV) band of heart rate (0.14-0.40 Hz) throughout a work day, were determined using multilevel analysis. Explanatory variables were analysed at two levels: at the lowest level (within-day level), the effects of positive mood, negative mood, demand, satisfaction, demand-satisfaction ratio, and time of day were assessed. At the highest level (the subject level), the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…Because they operate at diVerent frequencies, the actions can be identiWed by diVerent frequency spectra. Inability to unwind and recover is reXected on a low parasympathetic inXuence on HRV (Hanson et al 2001). A high level of HRV is advantageous from a health perspective, and especially a high level of high-frequency (HF) power is energy-saving for the heart because of rapid regulation of activity.…”
Section: Introductionmentioning
confidence: 99%
“…Because they operate at diVerent frequencies, the actions can be identiWed by diVerent frequency spectra. Inability to unwind and recover is reXected on a low parasympathetic inXuence on HRV (Hanson et al 2001). A high level of HRV is advantageous from a health perspective, and especially a high level of high-frequency (HF) power is energy-saving for the heart because of rapid regulation of activity.…”
Section: Introductionmentioning
confidence: 99%
“…provides data about the state of the subject's physiological system. The statistical analyses performed on aggregated data across epochs (usually as a mean of the above variables) attempt to make use of this information to investigate the differences regarding physiological system status between groups, during work, rest, sleep, and when subjected to demands (position, exertion, strain) [8,9]. However, to restrict these analyses to the mean values across time periods, the applied procedure ignores the next level of within-subject variation that occurs in the subjects physiological state.…”
mentioning
confidence: 99%
“…Taking into account that some authors have indicated that the physiological mechanism mediating work stress and CVD is not yet clarified (Hanson, Godaert, Maas & Meijman, 2001;Serrano, Moya-Albiol & Salvador, 2009;Diene et al 2012) our results provide more information about the evolution of variables that could be related to CVD and to emotional states during an academic year. However, the lack of response in BP and in C in our study and the lack of the expected relationships between PS with BP and C are difficult to explain.…”
Section: Discussionmentioning
confidence: 63%